IMPLEMENTATION OF MIND MAPPING IN IMPROVING SIXTH-GRADE STUDENTS’ DESCRIPTIVE WRITING ABILITY AT SDN BLIMBING 2 MALANG - Mochammad Amirudin Ichda; Shirly Rizki Kusumaningrum; Radeni Sukma Indra Dewi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article analyzes the influence of mind mapping in improving sixth-grade elementary school students’ descriptive writing ability. The type of research is qualitative research with a problem-solving research design. Problem-solving is an approach that indicates the data in the form of words or statements obtained through interviews, documentation, observations, and so on. Classroom action research is conducted to solve problems in learning in the classroom or to improve learning quality. The research subjects involved 24 students of class VI at SDN Blimbing 2. The test results before implementing the class research action indicate that the average value is 54. In cycle I, the average value is 68.7 with a completeness percentage of 42%. It shows that between the pretest and cycle 1 there is an increasing value of 14.7. In cycle 2, the average value increases to 75.2 with a completeness percentage of 100%. The observation results of students’ activity in cycle 1 achieve 71% while in cycle 2 it achieves 81%, which means that there is an increasing percentage of 10%. The observation results teacher’s teaching management in cycle 1 achieves a percentage of 73% and in cycle 2 it achieves a percentage of 87%, which means that there is an increasing percentage of 15%. Thus, the data analysis of students’ writing descriptive essays through mind mapping from the pretest, cycle 1 to cycle 2 has achieved an average score target.